The new wilderness [compact disc, unabridged] - Cook, Diane, 1976- (Harper Audio, 2020)
Bea's five-year-old daughter, Agnes, is slowly wasting away. The smog and pollution of the City, an over-populated, over-built metropolis where most of the population lives, is destroying her lungs. But what can Bea do? No one leaves the City anymore, because there is nowhere else to go. But across the country lies the Wilderness State, the last swath of open, protected land left. Here forests and desert plains are inhabited solely by wildlife. People are forbidden. Until now.